Kepemilikan Bank, Pemenuhan Kecukupan Modal Dan Insentif Pbv Sebagai Penentu Pengambilan Risiko Perbankan - - Taswan (Conference In Business, Accounting, And Management (CBAM), 2012)
This paper on these issues, the first effect of bank ownership on risk taking, the effect of Capital Adequacy Ratio (CAR) on risk taking, and the effect of PBV on risk taking. Issues were tested in the total sample and sub sample with PBV as risk-taking incentives. With a sample of commercial banks operating in Indonesia and and analyzed with the OLS model and the analysis of sub-group of the obtained results that the domestic private ownership, foreign ownership and ownership concentration of each of the significant positive effect on the risk. Negatively Capital Adequacy ratio (CAR) affect on risk taking, and PBV negative effect on risk taking. Influence the determinants of risk among groups of banks with low PBV with higher PBV is significantly different. Determinants of risk in the lower PBV of bank is more sensitive than the bank with a high PBV. This finding is consistent with the moral hazard argument or entrenchment, except for the effect of regulation on risk taking is more consistent with the arguments of representative and convergence.Keywords: Bank ownership, CAR, PBV, Risk, entrenchment.